Analysis of Regional Gross Domestic Product Per Capita, Population Density, and the Number of Motor Vehicles on Environmental Quality in Indonesia - N, Nisrina Atikah; Ramli, Ramli; Rahman, Arif (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Environmental quality plays an essential role in maintaining sustainability amid a country's economic activities. In Indonesia, environmental quality can be influenced by national sectoral economic activities, population density, and the number of motor vehicles. This study aims to analyze the effects of regional gross domestic product (RGDP) per capita, population density, and the number of motor vehicles on environmental quality in Indonesia. The observation period of this research spans from 2012 to 2023, aiming to determine whether these variables exert a positive or negative effect on environmental quality in Indonesia. The data analysis method employed is a spatial panel multiple linear regression model. This study adopts both descriptive and inferential research designs. The data utilized are secondary data obtained from Statistics Indonesia (BPS) and the Ministry of Environment and Forestry of the Republic of Indonesia. The findings indicate that RGDP per capita (PDRBK) has a positive effect on the Environmental Quality Index (IKLH) in Indonesia during the 2012-2023 period. Conversely, population density has a negative effect on IKLH during the same period, and the number of motor vehicles also negatively affects IKLH in Indonesia between 2012 and 2023.